Insights into the benefits of farmer led approaches in promoting sustainable agricultural intensification - Snyder, Katherine A.; Dittoh, Saa; Braslow, Juliet; Somda, Jacques; Nchor, Joseph ,; Doke, Dzigbodi; Ayambila, Sylvester ,; Atindana, Sandra; Mohammed, Afi Abujaja; Amoah, Samuel Twumasi; Obenewaah, Mercy Owusu ,; Lolig, Victor; et al. (2017)
Farmers make agricultural decisions based on a holistic understanding of their farm and it’s place in and interactions with the surrounding landscape. Because of this they often resist conventional agricultural intensification practices which they see as negatively impacting agricultural and environmental resources in the medium to long term. Ecosystem Based Management (EBM) practices have long-lasting positive effects on soils, water resources, trees, grasses and agricultural yields, and have multiple economic benefits that go beyond cash, to include ecosystem services, well-being and quality of life EBM should be adopted by women and men farmers and integrated into all agricultural and natural resource management planning and implementation Greater investment by government departments, and the development community, in EBM will have a significant, long term positive impact on food security, livelihoods and ecosystem health